THE RELATIONSHIP BETWEEN DETERMINANTS OF THE CAUSES OF HYPERTENSION IN PREGNANT WOMEN IN THE WORKING AREA OF THE CIRUAS HEALTH CENTER, SERANG REGENCY IN 2024 - Novianti; Ikhlasiah, Marthia; Lukman Waris (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
One of the dangerous diseases in pregnant women is hypertension. Hypertension is a cause of death for both mother and baby. Hypertension has no typical symptoms and signs as an early warning. In pregnancy with hypertension occurs when gestational age enters 20 weeks. This study aims to determine the factors associated with hypertension in pregnant women. Hypertension is a condition where the blood pressure of pregnant women is above more than 140 mmHg or diastolic blood pressure above 90 mmHg. This type of research is quantitative with a cross sectional design. Independent variables are age, education, knowledge, ANC examination, and history of hypertension. While the dependent variable is Hypertension. The population is all pregnant women in the working area of the Ciruas health center, Serang Regency in 2023. The sample number of 100 people was selected by purposive random sampling. Statistical test using Chi square test with 95% CI. The results of statistical tests showed that age and education variables did not have a significant relationship with hypertension in pregnant women (p > 0.05), while knowledge variables with p = 0.002, ANC examination with p = 0.014, history of hypertension with p = 0.001, which means it has a significant relationship with hypertension in pregnant women in the working area of the Ciruas health center, Serang regency in 2024.  The largest OR value is in the knowledge variable OR=6.366.